Germany and NATO missile defence: Between adaptation and persistence - Marcel Dickow; Katarzyna Kubiak; Oliver Meier; Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2016)
At the 2010 Lisbon summit, the NATO allies decided to develop a joint missile defence system as a core element of collective defence. Since then, the security environment has changed fundamentally. The hopes of cooperating with Moscow on missile defence have been shattered, while the nuclear deal with Iran reduces the threat from the south and thus undermines one of the central justifications for the proposed system. At the same time, the alliance has made progress in its efforts to protect its territory, forces and populations from missile attacks. While the fundamental decision to create a missile defence system is likely to hold, the German Bundestag should consider the foreign policy, security, industrial, arms control and financial implications before approving any additional German contributions. (SWP Comments)
Keywords: 320